2018
DOI: 10.1002/uog.17557
|View full text |Cite
|
Sign up to set email alerts
|

Screening for ovarian cancer: imaging challenges and opportunities for improvement

Abstract: The United Kingdom Collaborative Trial of Ovarian Cancer Screening (UKCTOCS) recently reported a reduction in the average overall mortality among ovarian cancer patients screened with an annual sequential, multimodal strategy that tracked biomarker CA125 over time, where increasing serum CA125 levels prompted ultrasound. However, multiple cases were documented wherein serum CA125 levels were rising, but ultrasound screens were normal, thus delaying surgical intervention. A significant factor which could contri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 148 publications
(161 reference statements)
0
62
0
1
Order By: Relevance
“…Obstetrics and gynecology been reported that in the United States alone more than 22 000 new ovarian cancer cases and 14 000 ovarian cancer deaths are recorded annually [3]. The main hurdles in the treatment of ovarian cancer are its late diagnosis and dearth of therapeutic targets.…”
Section: Basic Researchmentioning
confidence: 99%
“…Obstetrics and gynecology been reported that in the United States alone more than 22 000 new ovarian cancer cases and 14 000 ovarian cancer deaths are recorded annually [3]. The main hurdles in the treatment of ovarian cancer are its late diagnosis and dearth of therapeutic targets.…”
Section: Basic Researchmentioning
confidence: 99%
“…Many previous trials demonstrated a reduction in the average overall mortality among ovarian cancer patients screened with an annual sequential, multimodal strategy that tracked biomarkers CA125 over time, where increasing serum CA125 levels prompted ultrasound [20][21][22][23]. A critical factor which could contribute to false negatives is that many aggressive ovarian cancers are believed to arise from epithelial cells on the fimbriae of the fallopian tube, which are not readily imaged.…”
Section: Optionalmentioning
confidence: 99%
“…The ability to detect ovarian carcinomas before they metastasize is critical and future efforts toward improving screening should focus on identifying unique features specific to aggressive, early stage tumors, as well as improving imaging sensitivity to allow for detection of tubal lesions. So far, multimodal screening strategy in which blood-based assay is positive, and subsequent imaging examination may prove useful in detecting early stage cases [20][21][22]25].…”
Section: Optionalmentioning
confidence: 99%
“…e 5-year survival rate of earlystage ovarian cancer patients is more than 92%; however, the 5-year survival rate of late-stage ovarian cancer patients is only 29%, suggesting that early diagnosis is crucial for patient survival [2]. Unfortunately, only approximately 20-25% of patients with ovarian cancer are diagnosed at an early stage [3] due to a lack of early diagnostic markers [2]. Additionally, the molecular mechanism of ovarian cancer development is not fully understood.…”
Section: Introductionmentioning
confidence: 99%